Performance Comparison of PI and Fuzzy-PI Logic Speed Control of Induction Motor (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Single-phase induction motors are also used extensively for smaller loads. Speed control of induction motor has beenimplemented using PI (Proportional-Integral) controller and Fuzzy PI controller in Simulink MATLAB. The results showthat induction motor Fuzzy-PI speed control method results in a quicker response with no overshoot than the conventional PI controller. The settling time of induction motor Fuzzy-PI speed is better than the conventional PI controller. The integral time of weighted absolute error (ITEA) performance criteria also shows that the induction motor Fuzzy-PI speed control has better performance. Moreover, the induction motor Fuzzy-PI speed control has a strong ability to adapt to the significant change of system parameters.